(untitled) (Journal of Student Affairs in Africa, 2021)
This research sought to determine if a teaching intervention using tutors in a South African university could promote epistemological access to university for first-year students. Although hiring, developing and managing tutors takes money, time and energy, the effectiveness of tutors in the South African contex is underreported. The first-year class under study was diverse in terms of gender, race, ethnicity and geographical origin. The tutors were all postgraduate students, and similarly diverse. In terms of research design, student test results were compared from one test to another. The students also rated the tutors. Students who attended the majority of the assigned tutorials improved their marks by an average of 20%.Even students whose tutorial attendance was haphazard fared better academically than those who did not attend at all. Students who skipped all the tutorials saw a dramatic decline in their marks, suggesting that tutorial attendance should be obligatory. Individual tutors matter, however. It seems that some tutors can explain, facilitate understanding and engage their students better than others. Students assigned to such tutors achieved the greatest academic gains. Thus, recruitment strategies and tutor training are crucial. Tutor popularity (based on student ratings) did not correlate with positive academic improvements. Thus, student ratings should not by themselves strongly influence hiring decisions. In conclusion, resources allocated to tutors were worthwhile and the tutors enabled epistemological access for many.